Expanding the Reach of Geriatrics Grand Rounds Using Facebook Live. Issue 10 (1st October 2019) - Powers, Becky B.; Hartmann, Paul; Welch, Melissa; Ross, Jeanette
Abstract : See related editorial by Mandi Sehgal